Mimicking Human and Biological Skins for Multifunctional Skin Electronics. (13th August 2019) - Lee, Youngoh; Park, Jonghwa; Choe, Ayoung; Cho, Seungse; Kim, Jinyoung; Ko, Hyunhyub
Abstract: Electronic skin (e‐skin) technology is an exciting frontier to drive the next generation of wearable electronics owing to its high level of wearability, enabling high accuracy to harvest information of users and their surroundings. Recently, biomimicry of human and biological skins has become a great inspiration for realizing novel wearable electronic systems with exceptional multifunctionality as well as advanced sensory functions. This review covers and highlights bioinspired e‐skins mimicking perceptive features of human and biological skins. In particular, five main components in tactile sensation processes of human skin are individually discussed with recent advances of e‐skins that mimic the unique sensing mechanisms of human skin. In addition, diverse functionalities in user‐interactive, skin‐attachable, and ultrasensitive e‐skins are introduced with the inspiration from unique architectures and functionalities, such as visual expression of stimuli, reversible adhesion, easy deformability, and camouflage, in biological skins of natural creatures. Furthermore, emerging wearable sensor systems using bioinspired e‐skins for body motion tracking, healthcare monitoring, and prosthesis are described. Finally, several challenges that should be considered for the realization of next‐generation skin electronics are discussed with recent outcomes for addressing these challenges. Abstract : Biomimicry of human and biological skins has established a new paradigm for realizing novel wearable electronic systems with exceptional multifunctionality as well as advanced sensory functions. This comprehensive review focuses on emerging wearable sensor systems using bioinspired electronic skins mimicking unique geometries and sensory systems of the human and biological skins.